“We are competely dependent on them . . .” – relations between the helpers and the hiding as exemplified by Fela Fischbein’s diary - Barbara Engelking (Zagłada Żydów)
The text is an analysis of the relations between a hiding Jewess, Fela Fischbein, and her landlady, a Polish woman, Katarzyna Dunajewska. In hiding, Fela wrote her diary, which was the basis for the description of her feelings, experiences, her perception of the Poles who helped her, and her change of attitude toward them. The hiding Jewess moves from gratitude to the Poles to disappointment and aversion, which is caused by the attitude of the Poles to the Jews who needed help: financial exploitation of their situation and denouncing them to the Germans.